Geopolitical importance of the Central Bi-Oceanic Railway Corridor for Brazil - Peña Ríos, Yesica (2018)
This article addresses the geopolitical importance of the Central Bi-Oceanic Railway Corridor for Brazil, which responds to its geopolitical school, in which they emphasize territorial integrity and interconnection, its exit to the Pacific Ocean, its projection to Africa, its vision of being a global actor in the international system, among others. It follows the classic geopolitical approaches of Mahan, Mackinder, Haushofer and Cohen's new postulate, applied to the current dynamics of the international system and to the geopolitical aims of Brazil that contain geographical areas of strategic value for this State. Once this corridor is completed, Brazil will achieve its projection to the Asia-Pacific (area of global power dispute) and the interconnection of its territory through the development of infrastructure. In conclusion, Brazil reaffirms its belonging to a geopolitical region from which the powers of second order are born.   DOI: https://doi.org/10.31876/sl.v2i1.5